2021
DOI: 10.3390/diagnostics11081424
|View full text |Cite
|
Sign up to set email alerts
|

MRI of the Entire Spinal Cord—Worth the While or Waste of Time? A Retrospective Study of 74 Patients with Multiple Sclerosis

Abstract: Spinal cord lesions are included in the diagnosis of multiple sclerosis (MS), yet spinal cord MRI is not mandatory for diagnosis according to the latest revisions of the McDonald Criteria. We investigated the distribution of spinal cord lesions in MS patients and examined how it influences the fulfillment of the 2017 McDonald Criteria. Seventy-four patients with relapsing-remitting MS were examined with brain and entire spinal cord MRI. Sixty-five patients received contrast. The number and anatomical location … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
(43 reference statements)
3
5
0
Order By: Relevance
“…The distribution of SC lesions and atrophy across SC levels was a main objective of our study. In line with our results, further studies reported the highest frequency of lesions at the cervical enlargement ( Amezcua et al, 2013 , Bot et al, 2004 , Breckwoldt et al, 2017 , Galler et al, 2016 , Kidd et al, 1993 , Poulsen et al, 2021 , Weier et al, 2012 ). Of note, a recent study focusing on lesions in the corticospinal tract, covering the brain and upper cervical SC, also reported the highest frequency at C3/4 ( Kerbrat et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…The distribution of SC lesions and atrophy across SC levels was a main objective of our study. In line with our results, further studies reported the highest frequency of lesions at the cervical enlargement ( Amezcua et al, 2013 , Bot et al, 2004 , Breckwoldt et al, 2017 , Galler et al, 2016 , Kidd et al, 1993 , Poulsen et al, 2021 , Weier et al, 2012 ). Of note, a recent study focusing on lesions in the corticospinal tract, covering the brain and upper cervical SC, also reported the highest frequency at C3/4 ( Kerbrat et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…We found that lesions are commonly found at different spinal cord levels and are mostly inflammatory even in end-stage progressive MS. Previous MRI work has demonstrated a similar prevalence of spinal cord involvement to our study [7, 35, 44]. However, our study provides novel insight into the extent of inflammatory activity in spinal cord lesions at end-stage disease.…”
Section: Discussionsupporting
confidence: 83%
“…In general, this gradient of lesion prevalence along the entirety of the spinal cord recapitulates what has been seen in previous MRI studies of clinical cohorts. [20][21][22] However, our study identified many more thoracolumbar lesions. The fact that our study analyzed cases at the end of life may contribute to this discrepancy as our cohort has accumulated lesion burden throughout the length of the disease process.…”
Section: Discussionmentioning
confidence: 78%
“…The manuscript by Poulsen et al aimed at determining the distribution of MS lesions throughout the length of the spinal cord and how their detection can influence the diagnosis of MS [ 6 ]. Out of the 74 newly diagnosed MS patients, 58 already fulfilled the dissemination in space (DIS) criteria with just brain MRI scans alone [ 6 ]. When the cervical spinal cord scans were added, an additional 9 patients satisfied the DIS criteria.…”
mentioning
confidence: 99%
“…On the other hand, lesion analysis in the thoracic and lumbal spinal cord did not result in a significant increase in DIS diagnosis. The addition of cervical spinal cord imaging did not significantly influence the fulfillment of the dissemination in time (DIT) criteria when compared to the brain-MRI-only protocol [ 6 ]. Based on their findings, cervical cord scanning does improve the DIS evaluation and should be implemented in the process of MS diagnosis.…”
mentioning
confidence: 99%